2017
DOI: 10.1017/jfm.2017.770
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and mixing effects in hot jet initiation and propagation of hydrogen detonations

Abstract: In the present work, the role of diffusion and mixing in hot jet initiation and detonation propagation in a supersonic combustible hydrogen–oxygen mixture is investigated in a two-dimensional channel. A second-order accurate finite volume method solver combined with an adaptive mesh refinement method is deployed for both the reactive Euler and Navier–Stokes equations in combination with a one-step and two-species reaction model. The results show that the small-scale vortices resulting from the Kelvin–Helmholtz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The highest grid resolution in Case 2 of min Δ =7.8×10 -6 m, which corresponds to 275 Pts/Lhr (points per half reaction length), has been effectively verified in recent works [4,10]. It is reported that the viscous scale is the smallest among the three diffusive scales (viscous shear layer, thermal heat conduction layer and mass diffusion layer).…”
Section: Convergence Analysismentioning
confidence: 63%
See 2 more Smart Citations
“…The highest grid resolution in Case 2 of min Δ =7.8×10 -6 m, which corresponds to 275 Pts/Lhr (points per half reaction length), has been effectively verified in recent works [4,10]. It is reported that the viscous scale is the smallest among the three diffusive scales (viscous shear layer, thermal heat conduction layer and mass diffusion layer).…”
Section: Convergence Analysismentioning
confidence: 63%
“…It has been demonstrated that in straight channels overdriven detonation can attenuate to CJ detonation and dynamically stable propagation of detonation can be achieved when the supersonic incoming flow is given the corresponding CJ velocity after the shutdown of the hot jet [4]. Different from straight channels, the product in expanding channels is expected to expand more freely due to the Prandtl-Meyer expansion, which is theoretically able to result in further attenuation of CJ detonation and even detonation failure.…”
Section: Stabilization Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…With the adaptive mesh refinement method, AMROC can accurately resolve the flame front, shock wave, and detonation, and thus has been successfully applied to the extensive studies of combustion. 53,[58][59][60][61][62]…”
Section: Methodsmentioning
confidence: 99%
“…The present work uses the NS equations with the one-step chemistry model as governing equations [23]. Currently, it is very expensive to conduct high-resolution multidimensional detonation simulations solving the NS equations with detailed chemistry.…”
Section: A Governing Equationsmentioning
confidence: 99%